Negative Nominal Interest Rates and the Bank Lending Channel - Eggertsson, Gauti B; Juelsrud, Ragnar E; Summers, Lawrence H; Wold, Ella Getz (Review of Economic Studies, 2024)
Abstract We investigate the bank lending channel of negative nominal policy rates from an empirical and theoretical perspective. For the empirical results, we rely on Swedish data, including daily bank-level lending rates. We find that retail household deposit rates are subject to a lower bound (DLB). Empirically, once the DLB is met, the pass-through to mortgage lending rates and credit volumes is substantially lower and bank equity values decline in response to further policy rate cuts. We construct a banking sector model and use our estimate of the pass-through of negative policy rates to lending rates as an identified moment to parameterize the model and assess the impact of negative policy rates in general equilibrium. Using the theoretical framework, we derive a sufficient statistic for when negative policy rates are expansionary and when they are not.